Damage detection in acsr cables based on ultrasonic guided waves (2014)
The use of ultrasonic guided waves is growing as a non-destructive testing technique of multi-wire cables used in civil engineering structures. Wave propagation characteristics in these types of structures have been challenging to investigate owing to the load-dependent inter-wire contact and the helical geometry of the peripheral wires. In this work, experiments of guided waves propagated in a 0.9m Aluminum Conductor Steel Reinforced (ACSR) cable were conducted employing two longitudinal piezoelectric transducers attached to the ends of the cable in a through transmission configuration. Longitudinal L(0,1) and flexural F(1,1) modes were identified at 500 kHz via dispersion curves and Wavelet Transforms (WT). Experiments included artificial damage introduced in the middle of the cable by cutting and gradually increasing the cut depth from 1mm to 9mm. The attained results suggest a change of guided modes excitation and reception from F(1,1) to L(0,1) due to reduced friction contact among individual wires. This change of guided waves modes in response to damage variations, associated with the transmitted ultrasonic energy, was identified and discussed as potential mean of damage monitoring.